ALGORITHM FOR CHOOSING A STRATEGY FOR THE FORMATION AND DEVELOPMENT OF BRANDING OF AGRARIAN REGIONS - GAZUDA, Serhiі (Herald of Khmelnytskyi National University. Economic sciences, 2024)
An algorithm of the strategy of formation and development of branding of agrarian regions is built in the article, with a justification of the peculiarities of its functionality. It is noted that in the conditions of market management, the complexity of transformational changes, primarily due to the state of war and the unpredictability of external influences, the necessity of substantiating the strategy of formation and development of territory branding, in particular agrarian regions, is determined. The purpose of the study is to outline the algorithm for building and determining the functionality of the strategy for the formation and development of branding of agrarian regions. The main task of the research is the selection of a strategy, in particular the basic and functional one, as well as the identification of approaches to the implementation of the mechanism of formation and development of branding of agrarian regions with the indication of their individual functions. In the research process, general scientific methods of generalization and systematic analysis were applied to justify a differentiated approach to the selection of strategies, which will be based on branding criteria: the level of the value of the brand capital of the agrarian region; the level of brand premises and the level of branding effectiveness. It is proposed to choose a strategy for the formation of branding of agrarian regions and a strategy for the development of branding of agrarian regions. The model of branding of agrarian regions proposed by the author is outlined with scientific novelty and practical significance, which is based on the criterion of the value of the brand capital of an agrarian region, which allows a differentiated approach to the choice of a model of branding formation and a model of branding development, to individualize the choice of strategy, methods, tools and a system for ensuring the branding of territories .
Keywords: strategy; formation and development; agricultural regions; branding model; stakeholders; branding criteria; model selection; brand capital